Myqiraat / Syahidatul Fitriah Ishak, Zulkifly Mohd Zaki and Khairul Anuar Mohamad - Ishak, Syahidatul Fitriah; Mohd Zaki, Zulkifly; Mohamad, Khairul Anuar (Division of Research and Industry Linkages, 2017)
Often studying Qiraat is difficult without using any supplementary tool. Current practice is using traditional ways of learning; i.e. book references and the guidance from lecturers. The learning of Qiraat is necessary guided by the lecturers due to its nature of pronouncing the correct words and Tajweed in Quran. This makes the process o f learning Qiraat takes longer time than it should be. This will make it worse when time is a major constraint for both students and lecturers to spend more time together to comprehend the Qiraat learning, The aim of this project is to enable and promote the ubiquitous learning of the Qiraat using mobile device. This tool has been evaluated to ensure high acceptability among potential users when the application is deployed in real environment. Results show that most participants realized the potential benefits of the application. This includes a better understanding as well as encouraging and motivating the participants who wish to learn Qiraat anytime and anywhere. Perceptions from the participants on the designs are very positive to support the development of the real application.